Continent Ileostomy as an Alternative to End Ileostomy - Xian-rui Wu; Hao-xian Ke; Ravi P. Kiran; Bo Shen; Ping Lan (Gastroenterology Research and Practice)
Continent ileostomy (CI) was once a prevalent surgical technique for patients who required total proctocolectomy but then gave way to ileal pouch-anal anastomosis (IPAA) after 1980. Although IPAA has been the gold standard procedure preferred by most patients when total proctocolectomy is required, due to its imitation of physiological function of rectum and preserved function of anus, various complications have been observed with a relatively high rate of morbidity that could affect pouch longevity. Once serious complications such as pelvic abscesses and/or fistula occur, the pouch often needs to be removed. In addition, for some patients with a shortened small intestine or foreshortened mesentery, it is impossible for the ileal pouch to reach the pelvic floor, thus making the creation of an IPAA difficult. Previously, most of these patients would be referred for an end ileostomy, with an associated poor quality of life. In this circumstance, we propose that CI may deserve a reappraisal and serve as an alternative. In this article, we review the indications, contraindications, technique evolution, and outcomes of CI.